Transcranial Access Using Fluoroscopic Flat Panel Detector CT Navigation - Cooke, D.L.; Levitt, M.; Kim, L.J.; Hallam, D.K.; Ghodke, B. (American Journal of Neuroradiology, 2011)
SUMMARY: FPCT and navigation software on contemporary fluoroscopic units perform imaging of a quality comparable with conventional CT. They can accurately guide percutaneous procedures, providing live instrument visualization and the capability to re-image without patient transfer. FPCT navigation was used in the placement of a ventricular drain in a 62-year-old woman for subarachnoid-related hydrocephalus by using an otherwise standard bedside technique. Ventriculostomy catheter placement was technically successful without complication with a catheter at the foramen of Monro. DSAdigital subtraction angiographyFPCTflat panel detector CT